Answer:
A
Step-by-step explanation:
6x+3y=33 <=> 2x+y=11<=>4x+2y=22 (1)
4x+y=15 (2)
(1)-(2) <=> y=7
Answer:
Step-by-step explanation:
2x * 2x = 4x^2 and -11 * 11 = -121
Answer:
i think it's 10 but i might be wrong
Step-by-step explanation:
There are 9+7+6=22 marbles in total. The probability of selecting a yellow marble would be 9/22. By replacing that yellow marble with a green marble, you aren't changing the total marble count, so the probability of selecting a green marble would be 7/22. Because the two events are independent, their probabilities will get multiplied. Therefore, P(Yellow, then Green) = P(Yellow) * P(Green) = 9/22 * 7/22 = 63/484.